A novel approach to synchronization conditions for delayed chaotic Lur'e systems with state sampled-data quantized controller. Issue 14 (September 2020) - Wu, Tao; Park, Ju H.; Xiong, Lianglin; Xie, Xueqin; Zhang, Haiyang
Abstract: This paper, by designing a state quantized sampled-data controller (SQSDC), studies the synchronization issue for delayed chaotic Lur'e systems (CLSS). A novel method, the auxiliary function-based-inequality Lyapunov–Krasovskii functional (LKF), is for the first time to be introduced. This method can make the best of more the obtainable information about the practical sampling pattern in comparison with some existing approaches. A new zero-valued equation, which increases the combinations of some resulting vectors, is firstly formulated. According to the novel method and zero-valued equation, some new master-slave synchronization (MSS) conditions are established. Meanwhile, the corresponding SQSDC gain matrix is obtained with the bigger sampling interval (SI) than those in the existing works. Finally, the effectiveness and advantages of the proposed method are shown by two numerical examples.